2023
DOI: 10.1021/acs.inorgchem.2c03903
|View full text |Cite
|
Sign up to set email alerts
|

Selective, Disruptive Luminescent Ru(II) Polypyridyl Probes of G-Quadruplex

Abstract: Sensors capable of transducing G-quadruplex DNA binding are important both in solution and for imaging and interrogation in cellulo. Ru(II)-based light switches incorporating dipyridylphenazine (dppz) ligands are effective probes for recognition and imaging of DNA and its polymorphs including G-quadruplex, although selectivity is a limitation. While the majority of Ru(II)-based light switches reported to date, stabilize the quadruplex, imaging/theranostic probes that can disrupt G4s are of potentially enormous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
1
3
0
Order By: Relevance
“…Most reported metal complex peptide conjugates, certainly all reported to date by our group, undergo cell uptake by endocytosis or active transport, where the uptake was observed to switch off at 4 °C, indicating an energy-dependent pathway. 23 , 29 , 63 , 64 By contrast here, all three compounds remained strongly cell permeable at 4 °C and imaging following 1 h incubation confirmed, uniquely in our experience, that the mechanism of uptake is energy independent. This accounts for the rapid uptake by live cells.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Most reported metal complex peptide conjugates, certainly all reported to date by our group, undergo cell uptake by endocytosis or active transport, where the uptake was observed to switch off at 4 °C, indicating an energy-dependent pathway. 23 , 29 , 63 , 64 By contrast here, all three compounds remained strongly cell permeable at 4 °C and imaging following 1 h incubation confirmed, uniquely in our experience, that the mechanism of uptake is energy independent. This accounts for the rapid uptake by live cells.…”
Section: Resultssupporting
confidence: 81%
“…Consequently, they tend to be less efficient singlet oxygen sensitizers than metal porphyrins, for example, whose PS efficiency is well established . But, Ru­(II) complexes owing to their synthetic versatility, can be tailored to offer the aforementioned advantages of lower dark cytotoxicity and cell targeting. , Means to promote singlet oxygen sensitization in such complexes include increasing the triplet character of the excited state, e.g., through mixing 3 LC states with the 3 MLCT state, by reducing singlet–triplet mixing of the 3 MLCT state or by enhancing the 3 MLCT lifetime. The latter is accomplished by manipulation of the relative energy of the triplet metal-centered state whose thermal population, likely to be promoted in the warm cellular environment, increases non-radiative decay.…”
Section: Introductionmentioning
confidence: 99%
“…27,59,[100][101][102][103] Given that such studies have included transition metal complexes as binding substrates, 25,104 and previous work within the Thomas group has identified Ru II complexes that bind to quadruplex-folded human telomere sequence (HTS) with high affinities, 21,22,105,106 analogous experiments were carried out with 1 and 2. These were of particular interest as a very recent report from the Keyes group 107 has shown that a Ru II -complex containing a ligand derived from phen-DC3 108 a high-affinity quadruplex-binding substrate 109 that has some structural similarities to qtpyactually disrupts quadruplex structures. The addition of HTS to solutions of 1 and 2 also resulted in quenching, Fig.…”
Section: Binding To Quadruplex Dnamentioning
confidence: 99%
“…Many fluorescent probes to detect DNA G-quadruplexes have been reported, and employed to image living cells [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In 2015, naturally occurring alkaloid epiberberine was found to emit fluorescence upon the binding with DNA G-quadruplex [ 58 ].…”
Section: Dna G-quadruplexes In Human Telomerementioning
confidence: 99%